2022
DOI: 10.3390/ijerph192315426
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Behavioural Alterations Induced by Arsenic and Temperature in Hediste diversicolor of Different Growth Stages

Abstract: Contamination with Arsenic, a toxic metalloid, is increasing in the marine environment. Additionally, global warming can alter metalloids toxicity. Polychaetes are key species in marine environments. By mobilizing sediments, they play vital roles in nutrient and element (including contaminants) cycles. Most studies with marine invertebrates focus on the effects of metalloids on either adults or larvae. Here, we bring information on the effects of temperature increase and arsenic contamination on the polychaete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…An H. diversicolor burrowing impairment could provide information on the potential increased susceptibility of these organisms (e.g., inability to avoid predators), as well as on potential effects on the community [77], since a potential impact or total impairment of burrowing/feeding activity affects nutrient resuspension and the oxygenation of sediment. In this study, no mobility issues were observed during burrowing assays, with organisms moving in circular motions along the edge of the container; therefore, the inability to move cannot be the reason for their altered burrowing behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An H. diversicolor burrowing impairment could provide information on the potential increased susceptibility of these organisms (e.g., inability to avoid predators), as well as on potential effects on the community [77], since a potential impact or total impairment of burrowing/feeding activity affects nutrient resuspension and the oxygenation of sediment. In this study, no mobility issues were observed during burrowing assays, with organisms moving in circular motions along the edge of the container; therefore, the inability to move cannot be the reason for their altered burrowing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study revealed that juveniles showed high sensitivity to protein damage, with a general significant increase in PC levels in exposed organisms indicating that SOD, CAT, and GST activities, although increased, could not prevent oxidative damage. These endpoints have been shown to be sensitive in H. diversicolor exposed to arsenic [77] and to the combination of arsenic and PS NPs [96], Ficopomatus enigmaticus exposed to carboxylated carbon nanotubes [97], and Diopatra neapolitana worms exposed to trace elements (arsenic, zinc, iron, manganese, lead, and tin) [98]. LPO, a parameter associated with greater production of free radicals, which can lead to an increase in the permeability of the cell membranes, rupture, and possible cell death, was, in general, lower than in the controls.…”
Section: Discussionmentioning
confidence: 99%